2021
DOI: 10.1007/s00296-021-04896-2
|View full text |Cite|
|
Sign up to set email alerts
|

COVID-19 and eosinophilic granulomatosis with polyangiitis or COVID-19 mimicking eosinophilic granulomatosis with polyangiitis?

Abstract: Coronavirus disease 2019 (COVID-19) and eosinophilic granulomatosis with polyangiitis (EGPA) share similarities in clinical, imaging findings and may present with respiratory distress. Differentiating a new-onset EGPA from COVID-19 during the current pandemic is a diagnostic challenge, particularly if other EGPA symptoms are overlooked. Here in this study we reviewed the literature regarding EGPA patients with COVID-19 and patients who diagnosed with EGPA or suffered an EGPA flare mimicking COVID-19. We condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…However, there is no strong evidence about the role of SARS-CoV-2 in the pathophysiology of vasculitis. EGPA and COVID-19 share common symptoms and some EGPA patients mimic COVID-19 features, which makes it challenging to distinguish them from each other [ 15 ]. So far, there is no report of EGPA after COVID-19 recovery and our report is the first one.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no strong evidence about the role of SARS-CoV-2 in the pathophysiology of vasculitis. EGPA and COVID-19 share common symptoms and some EGPA patients mimic COVID-19 features, which makes it challenging to distinguish them from each other [ 15 ]. So far, there is no report of EGPA after COVID-19 recovery and our report is the first one.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports imply a relation between COVID-19 infection and development of new onset AAV [ 15–18 ]. Furthermore, COVID-19 and AAV share some similar features, particularly regarding pulmonary involvement, which seemingly created a diagnostic challenge for AAV during the pandemic [ 19–21 ]. In our study, presence of hematuria (43.0% vs 75.0%; p = 0.084) and alveolar hemorrhage reported in thorax CT (1.3% vs 12.5%; p = 0.045) were observed to be increased in ANCA-positive patients which may be indicative of a vasculitic process.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, presence of hematuria (43.0% vs 75.0%; p = 0.084) and alveolar hemorrhage reported in thorax CT (1.3% vs 12.5%; p = 0.045) were observed to be increased in ANCA-positive patients which may be indicative of a vasculitic process. None of our ANCA-positive patients had eosinophilia, which could have been indicative of eosinophilic granulomatosis with polyangiitis development [ 19 ]. Moreover, histopathologic evaluation did not reveal a vasculitic involvement in the ANCA-positive patient who underwent renal biopsy in our study and none of the patients, in whom alveolar hemorrhage was reported in imaging, underwent bronchoalveolar lavage for confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of rituximab in AAV in the context of COVID-19 vaccines requires a balancing of risk–benefit ratio considering that humoral immune responses to COVID-19 vaccines could be dampened if such vaccines are administered in close proximity to the timing of rituximab [ 24 ]. The emergence of AAV following COVID-19 or AAV mimicking COVID-19 is also being increasingly recognized [ 25 , 26 ]. This clinical situation poses a further challenge for the management of patients with AAV during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%